Multi-omics analysis of LAMB3 as a potential immunological and biomarker in pan-cancer - Wang, Yanghao; Li, Guoyu; Wang, ZhiYuan; Wang, Weizhou; Wang, Xiaofang; Luo, Xuan; Zhao, Juan; Li, Fangfang; Bian, Li (Frontiers in Molecular Biosciences, 2023)
Laminin Subunit Beta 3 (LAMB3) is a transcription factor and participates in the coding of laminin. It plays an important role in cell proliferation, adhesion, and transfer by regulating various target genes and signaling pathways. However, the role of LAMB3 in human pan-cancer immunology and prognosis is still poorly understood. The TCGA, GTEx, CCLE, and HPA databases were utilized for the analysis of LAMB mRNA and protein expression. The expression of LAMB3 in various immune and molecular subtypes of human cancer was examined using the TISIDB database. The prognostic significance of LAMB3 in various cancers and clinical subtypes was investigated using Kaplan-Meier and Cox regression analysis. The relationship between LAMB3 expression, various immune cell infiltration, immune checkpoints, tumor mutational load, microsatellite instability, and DNA methylation was examined using the TCGA database. Clinical samples of four lung cancer cell lines and eight lung cancer cases were collected to confirm the expression of mRNA in lung cancer. In 17 cancers, the mRNA for LAMB3 is expressed differently and has good diagnostic and prognostic value in 22 cancers. Cox regression and Nomogram analysis show that LAMB3 is an independent risk factor for 15 cancers. LAMB3 is implicated in a variety of tumorigenesis and immune-related signaling pathways, according to GO, KEGG, and GSEA results. LAMB3 expression was associated with TMB in 33 cancer types and MSI in 32 cancer types, while in lung cancer LAMB3 expression was strongly associated with immune cell infiltration and negatively correlated with all seven methylated CpG islands. Cellular experiments demonstrated that LAMB3 promotes malignant behavior of tumor cells. Preliminary mechanistic exploration revealed its close association with PD-L1, CTLA4, cell stemness This is a provisional file, not the final typeset article gene CD133 and β-catenin-related signaling pathways. Based on these findings, it appears that LAMB3 could be a potential therapeutic target for immunotherapy and tumor prognosis. Our findings reveal an important role for LAMB3 in different cancer types.